Investigation on chemical composition, anticholinesterase and antioxidant activities of extracts and essential oils of Turkish Pinus species and pycnogenol - Ustun, Osman; Senol, Fatma Sezer; Kurkcuoglu, Mine; Orhan, Ilkay Erdogan; Kartal, MURAT; KARTAL, MURAT; Baser, Kemal Husnu Can (My University, 2012)
In the current work, the acetone, ethyl acetate, and ethanol extracts and essential oils of the twigs and needles of five Turkish Pinus species; P. brutia, P. halepensis, P. nigra, P. pinea, and P. sylvestris along with pycnogenol (the bark extract of P. pinaster) were examined for their inhibitory effects against acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) at 200 mu g mL(-1). Their antioxidant activity was tested using 2,2-diphenyl-1-picrylhydrazyl (DPPH) and N,N-dimethyl-p-phenylendiamine (DMPD) radical scavenging, metal-chelation, and ferric-reducing antioxidant power (FRAP) assays. Total phenol and flavonoid contents of the extracts were determined by Folin-Ciocalteau and AlCl3 reagents, respectively. GC-MS technique was applied for compositional profile of the essential oils of the tested species. Accordingly, the best AChE and BChE inhibition was caused by the twig essential oil (83.91 +/- 3.95%) and the needle ethanol extract (82.47 +/- 5.57%) of P. halepensis, respectively. Pycnogenol also caused a remarkable inhibition against AChE (63.33 +/- 0.22%) and BChE (83.67 +/- 0.22%). The extracts and essential oils usually showed a strong activity in the antioxidant assays. Pycnogenol exhibited a potent antioxidant effect and had the richest total phenol content. In the essential oils, alpha- and beta-pinene were identified the major components. These results reveal that the Pious species and pycnogenol are the potential sources of active metabolites with cholinesterase and antioxidant properties. (C) 2012 Elsevier B.V. All rights reserved.